Use of Cancer Screening by African Immigrants in NC. - OPOKU-DAPAAH, EDWARD (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
Advancement in screening has revolutionized cancer treatment in the USA and has been linked to successful detection and prevention of diverse forms of cancer. However, studies have focused on its use by majority groups, ignoring third-world immigrants, who typically arrive with little exposure to advanced medicine and scant knowledge about cancer screening. This study examined the use of cancer screening by African immigrants in North Carolina. It found that most respondents had used cancer screening; moreover, most have complied with screening protocols established by the American Cancer Society. However, some respondents appear to have been discouraged from screening by pre-arrival, African values about dangerous diseases, misperceptions, and denial of entitlements.